Effects of surfactant properties on pore wetting of membrane distillation - Connor Coolidge; Azal Mohammed Hassan Alhadidi; Wei Wang; Tiezheng Tong (Journal of Membrane Science Letters, 2024)
Pore wetting is a major constraint to the performance of membrane distillation (MD) for hypersaline brine treatment. Despite the existence of surfactants with diverse properties, an explicit relationship between the properties of surfactants and their capabilities of inducing pore wetting has yet to be established. In this study, we perform a comparative analysis of the wetting behaviors of various surfactants with different charges and molecular weights in MD desalination. The induction time of surfactants to initiate pore wetting was correlated to the apparent contact angle and surface tension of the feedwater. Our results show that different surfactants resulting in similar feedwater surface tensions can lead to drastically different wetting potential, suggesting that both charge of the head group and molecular weight of surfactants have a significant influence on membrane pore wetting. Further, we demonstrate that parameters that have been commonly used to indicate wetting potential, including apparent contact angle and solution surface tension, are not reliable in predicting the wetting behavior of MD membranes, which is intricately linked with surfactant properties such as charge and molecular size. We envision that our results not only improve our fundamental understanding of surfactant-induced wetting but also provide valuable insights that necessitate thorough consideration of surfactant properties in evaluating wetting potential and membrane wetting resistance for MD desalination.